New Hemilophini, Aerenicini and Calliini from French Guiana, transference and notes on Hemilophini (Coleoptera, Cerambycidae, Lamiinae) - Tavakilian, Gérard L.; Santos-Silva, Antonio (Zootaxa, 2019)
Two new genera and four new species of Hemilophini are described from French Guiana: Guyarolea lalannecassoui, gen. nov., sp. nov.; Cendiunopsis garnieri, gen. nov., sp. nov.; Isomerida fourneti, sp. nov.; Lapazina arnaudi sp. nov. Differences between Isomerida albicollis (Laporte, 1840) and I. invicta Galileo & Martins, 1996, are commented. Phoebemima Tippmann, 1960 is transferred to Aerenicini, and a new species is described from French Guiana: P. durantoni, sp. nov. A new genus and new species of Calliini is described from French Guiana: Hemilophopsis simius, sp. nov. A key to species of Lapazina is provided. The three new genera and Phoebemima durantoni are included in previous keys.